RESEARCH OF SPEED-STRENGTH QUALITIES OF SPECIFIC MUSCLE GROUPS IN ROWERS - Daniela Oronova; Oleg Hristov; Nikola Gospodarski; Rumian Hristov (Scientific Publishing House. NSA Press, 2018)
The power of the stroke in rowing is one of the main factors which determines good sport results. In this relation, increasing of power is а key task during rowers' muscular and strength training. The main purpose of the current research was to determine speed-strength ability of specific muscle groups of rowers, performing specific strength exercises: bench pull, squat and clean pull. Methods of the experiment include measurement of velocity and power in different load levels using Gym Aware device and its adjoining software Gym Aware Cloud. The received results demonstrate the specific strength and velocity abilities of the muscular groups which are involved in these movements. It was determined that the maximal power of each of them is achieved at a different point in the range of its working velocity. In squat the maximal power is in the range of the highest velocity achieved with small resistance, in bench pull the maximal power is achieved in the middle of the velocity range and in the clean pull it is achieved at a big resistance and at low velocity. These results arise lots of questions for further discussions.